Failure‐Experiment‐Supported Optimization of Poorly Reproducible Synthetic Conditions for Novel Lanthanide Metal–Organic Frameworks with Two‐Dimensional Secondary Building Units. Issue 66 (15th November 2021) - Kitamura, Yu; Terado, Emi; Zhang, Zechen; Yoshikawa, Hirofumi; Inose, Tomoko; Uji‐i, Hiroshi; Tanimizu, Masaharu; Inokuchi, Akihiro; Kamakura, Yoshinobu; Tanaka, Daisuke
Abstract: Invited for the cover of this issue are Daisuke Tanaka at Kwansei Gakuin University and co‐workers at Kwansei Gakuin University, Hokkaido University, Kyoto University, Japan and KU Leuven, Belgium. The image is a depiction of exploring the desired crystal by decision tree analysis. Read the full text of the article at 10.1002/chem.202102404 . Abstract : " We could promote research at the interface between data science and synthetic chemistry through the cooperation of experts from different fields ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 16347 ff. (DOI: 10.1002/chem.202102404 ).